2021
DOI: 10.1371/journal.pone.0248383
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal intubation of COVID-19 patients by paramedics using a box barrier: A randomized crossover manikin study

Abstract: Background In the prehospital setting, endotracheal intubation (ETI) may be required to secure the coronavirus disease 2019 (COVID-19) patient airway. It has been suggested that the use of a protective barrier can reduce possible aerosol delivery from patients to clinicians during ETI. We sought to assess the performance of ETI by paramedics wearing personal protective equipment with and without the use of a box barrier. Methods A randomized, crossover simulation study was performed in a simulation laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Additionally, simulation studies show that intubation is a safe procedure, provided that the healthcare professional is wearing PPE. However, to complicate the analysis, the wearing of PPE during the procedure may itself result in prolonged time to resuscitation [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, simulation studies show that intubation is a safe procedure, provided that the healthcare professional is wearing PPE. However, to complicate the analysis, the wearing of PPE during the procedure may itself result in prolonged time to resuscitation [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…38 When dealing with preventive measures during OTI, studies mostly bring the use of protective barriers in association with the use of PPE: devices in box format, plastic and cover that cover the patients' headboard. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]32,33,35 The hypothesis raised is that only the use of PPE does not adequately protect, requiring the association of protective barriers to ensure safety. 36 Intubation boxes are acrylic boxes containing two where the allocates the arms for access to the airway, and an opening in its lower portion to attach the patients' head.…”
Section: Resultsmentioning
confidence: 99%
“…The use of an aerosol box in the intubation procedure has been shown to increase the duration of the intubation procedure. 9 However, some literature mentions the benefits of protection and a reduction in the risk of contamination with the use of appropriate personal protective equipment along with the use of an aerosol box. This is in line with the research of Begley et al, who found that the average intubation with the aerosol box was 10 seconds longer than without the aerosol box (52.4 seconds compared to 42.9 seconds).…”
Section: Discussionmentioning
confidence: 99%